PENANAMAN TANAMAN OBAT KELUARGA (TOGA) DI LINGKUNGAN MEUNASAH SEBAGAI SUMBER OBAT ALAMI MASYARAKAT GAMPONG RAYEUK PIRAK, KECAMATAN MATANG KULI, KABUPATEN ACEH UTARA - Dwitya, Yonadiah; Boangmanalu, Andre M.; Navia, Zidni Ilman (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
The pharmacy in Gampong Rayeuk Pirak has an uncertain opening schedule. Therefore, it is necessary to plant Family Medicinal Plants (TOGA) which are essentially nutritious plants planted on yard land managed by families. TOGA is grown in order to meet the family's needs for traditional medicines that can be made by themselves. The purpose of this community service is to socialize and provide understanding to the gampong community about the importance of TOGA in their yards. The plants that are the focus of this activity are Curcuma Longa L., Zingiber Officinale, Kaempferia galanga, Amaranthus caudatus, Ipomoea reptans, dan Capsicum Frutescens L.